Veno-occlusive disease of the liver and Australia antigen - Pırnar, Aysel; Tınaztepe, Behçet; Koçak, Nurten (The Turkish Journal of Pediatrics, 1972)
A case of veno-occlusive disease in whom Australia Antigen was found to be positive, is presented. The possibility of viral infections being among the etiological agents of this disease is discussed and the related literature is reviewed.